Fertilization and Irrigation Needs for Florida Lawns and Landscapes - R. Klein; A. J. Lindsey; M. McMillan; J. B. Unruh; M. D. Dukes (EDIS)
Florida Friendly Landscaping™ Best Management Practices (BMPs) for management of commercial and residential lawns and landscapes were developed by scientists with the University of Florida’s Institute of Food and Agricultural Sciences (UF/IFAS). These BMPs assist homeowners and professionals in making management choices that will help sustain lawns and landscapes in Florida without impairing Florida’s water resources.